To be black and woman: dual vulnerability to STD/HIV/AIDS - Santos, Naila Janilde Seabra (Saúde e Sociedade, 2016)
The aim of this paper is to discuss the determinants of the vulnerability of black women to HIV/AIDS. By describing and analyzing socioeconomic data, incidence and mortality by AIDS and other diseases, we have drawn an epidemiological framework that emphasizes health inequities of black people, particularly black women. When compared to white women, black women have repeatedly increased risk of illness and death. The discussion of sexual and domestic violence reiterates disparities and social vulnerability of the black women. Socioeconomic inequalities and institutional racism are explanatory hypotheses for the high vulnerability of black women to STD/AIDS. Only a wide range of multisectoral actions, incisive facing of institutional racism by the governments and strengthening of the social movement will allow the beginning of a long journey to reach the principle of equity in health.